The Limitations of Locus Specific Methylation Qualification and Quantification in Clinical Material - Wojdacz, Tomasz K. (Frontiers in Genetics, 2012)
Despite the fact that terms: methylation quantification and qualification sound self-explanatory they are not easy to define. There are three main reasons for difficulties in understanding methylation status measurement. Firstly the complexity of the sequence specific methylation patterns oscillating between unmethylated, fully methylated and heterogeneously methylated. Secondly the technologies used to quantify and/or qualify the methylation, frequently give limiting results, which can easily be over or under interpreted. And lastly the specifications of the clinical samples used in laboratory practice frequently hamper the methylaton measurement. Therefore, the interpretation of methylation quantification and qualification depends on the particular experiment and has to be discussed with consideration of the specific locus, methodology used and the clinical material source. The question of the clinical significance of different methylation levels is even more complicated with a lot of evidence for correlation of qualitative methylation changes and clinical features of the disease and no data showing that different relative levels of methylation in clinical material alter the disease outcome. The current terminology and limitations with regard to methylation quantification and qualification are discussed in this paper.